The Distributive Effects of Corruption*. Issue 2 (12th February 2014) - Popa, Mircea
<x content-type="archive" xml:space="preserve">Abstract</x> This article puts forward an explanation of the resilience of corruption by arguing that this phenomenon offers net gains to a much larger share of the population than just corrupt government officials. Corruption is modeled as a solution to an allocation problem for a generic government good G. The defining features of this solution are the existence of a market for G when it is not supposed to exist, and the fact that, in that market, contracts cannot be enforced by an outside agent and transactions are usually secret. Corruption redistributes welfare toward 'insiders' who share some natural connection to the government and to other insiders. Corruption also redistributes welfare toward those who are skilled at imposing negative externalities.